2006
DOI: 10.1016/j.bbamem.2006.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic aspects of CPP-mediated intracellular drug delivery: Relevance of CPP self-assembly

Abstract: In recent years, cell-penetrating peptides have proven to be an efficient intracellular delivery system. The mechanism for CPP internalisation, which first involves interaction with the extracellular matrix, is followed in most cases by endocytosis and finally, depending on the type of endocytosis, an intracellular fate is reached. Delivery of cargo attached to a CPP requires endosomal release, for which different methods have recently been proposed. Positively charged amino acids, hydrophobicity and/or amphip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
194
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(198 citation statements)
references
References 116 publications
3
194
0
1
Order By: Relevance
“…Analysis of the secondary structure of the entire ␥-zein protein by CD spectra in aqueous media showed that the whole protein has a high helical content but a low PPII conformation content, at 55 and 7%, respectively (57). In contrast, the synthetic peptide (PPPVHL) 8 , corresponding to the repeat region, has been shown to adopt an amphipathic polyproline II conformation (27,44) and has been linked to a new family of cell-penetrating peptides (58). We demonstrate here that the repeat region of Zera is required for Zera-ECFP assembly, suggesting that the amphipathic character of Zera facilitates proper molecular orientation in the aqueous environment of the ER to optimize interchain disulfide bond cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the secondary structure of the entire ␥-zein protein by CD spectra in aqueous media showed that the whole protein has a high helical content but a low PPII conformation content, at 55 and 7%, respectively (57). In contrast, the synthetic peptide (PPPVHL) 8 , corresponding to the repeat region, has been shown to adopt an amphipathic polyproline II conformation (27,44) and has been linked to a new family of cell-penetrating peptides (58). We demonstrate here that the repeat region of Zera is required for Zera-ECFP assembly, suggesting that the amphipathic character of Zera facilitates proper molecular orientation in the aqueous environment of the ER to optimize interchain disulfide bond cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…Escape of some CPPs or viruses from early/late endosomes into the cytosol before its merging with lysosomes depends on acidification of endosomes. The acidic pH in the endosome alters the conformation of the CPPs or the N-terminal region of influenza virus hemagglutinin-2 (HA2) to induce destabilization of lipid membranes, facilitating the escape from the endosomes into the cytosol [35]. At this point, the exact mechanism of how 3D8 scFv escapes from caveolae/caveosome compartments into the cytosol, while maintaining its biochemical activity, is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…A nonendocytotic, receptor-free, energyindependent cellular process is another mechanism of the CPP translocation across biologic membranes, including formation of inverted micelles, direct translocation through the lipid bilayer, and pore formation on the membrane [46,47,55,56]. CPPs with high content in cationic residues are first absorbed at the cell surface to the numerous anionic moieties, such as sialic or phospholipidic acid or heparan sulfate proteoglycans [46,57]. Which of these mechanisms a CPP will use is dependent on such parameters as concentration, size (with cargo), temperature, cell type, and modifications of CPPs or their cargo [43,46,55].…”
Section: The Cytotoxicity Of the Synthesized Cpps And The Correspondimentioning
confidence: 99%